(untitled) (Architecture Image Studies, 2026)
This paper explores the Chinese digital service trade (DST) and examines its competitiveness through Porters Diamond Model considering the latest developments in technologies, such as the 5G network, Internet of Things (IoT), and artificial intelligence (AI). Through multidimensional indices (Revealed Comparative Advantage, Trade Competitiveness, Market Share, Michaely Fluctuation Index) and Entropy-TOPSIS method, we identify the impact of trade freedom, government efficiency, digital infrastructure, and industry openness on DST competitiveness. The findings indicate that China has an escalating degree of competition because of the robust digital foundation and trade incorporation, and integration of trade and DST exports has a high positive long-run enhancement to the growth of the importing countries. The research fills the significant gaps in the existing research on the role of digital trade rules and technology to determine the effects of global trade, particularly in developing markets. Examples such as the USMCA and the DEPA show that the fragmentation of regulations due to the current debate on whether goods or services ought to be classified as digital transmissions is hindering global governance initiatives. Our study offers a policy recourse to developing countries that seek to reduce institutional barriers and enhance competitiveness by adopting digital trade rule-making and digital investments in infrastructure, which will lead to inclusive growth in international trade.